"Owning" Knowledge: Looking Beyond Politics to Find the Public Good. Issue 177 (March 2017) - Bernstein‐Sierra, Samantha
Abstract : This chapter explores the theoretical assumptions underlying both the IP system and its counternarrative, academic openness, to encourage stakeholders to look beyond extremes as depicted in political rhetoric, and find a compromise consistent with the common mission of faculty, universities, and publishers.